DESAIN TAMAN VERTIKAL DENGAN KONSEP URBAN FARMING UNTUK FASADE PADA CLUSTER PERUMAHAN DI LOWOKWARU - Masito, Masito; Setyabudi, Irawan; Alfian, Rizki (Fakultas Pertanian, 2019)
Housing in Lowokwaru is a housing that is strategically located with a modern form and has enough land to arrange a park. On the housing estate there is also a narrow housing area and function shifting for each land in its use, so the solution of this research wants narrow land use with the concept of verticulture and urban farming, in housing facade clusters in poor lowokwaru using qualitative methods with sampling 20 houses which is around the lowokwaru sub-district of Malang city. This form of the results of the research design itself applies various designs that are suitable for the size of the house and the sampling of the housing. This research forms a design that makes the home page in accordance with its functions and residents of the house can carry out activities according to their needs such as farming in front of the house. verticultural application in lowokwaru housing, with designs such as verticulture of walls, vertical culture, vertical culture of fences, vertical shelf culture, hydropinics and aquaponics can overcome the problem of the function of a garden. Perumahan di daerah kecamatan lowokwaru merupakan perumahan yang letaknya strategis dengan bentuk yang modern dan mempunyai lahan yang cukup untuk menata sauatu taman. Pada lahan perumahan tersebut ada juga lahan perumahan yang sempit dan pengalihan fungsi untuk setiap lahan dalam penggunaanya. Penelitian ini ingin pemanfaatan lahan sempit dengan konsep vertikultur dan urban farming,dalam cluster fasade perumahan di lowokwaru malang yang menggunakan motode kualitatif dengan pengambilan sample 20 rumah yang ada di kecamatan lowokwaru kota malang. Hasil penelitian ini menerapkan berbagai desain yang sesuai dengan ukuran rumah dan pegambilan sample pada perumahan tersebut. Penelitian ini membentuk suatu desain yang membuat halaman rumah sesuai dengan fungsinya dan penghuni rumah dapat melakukan aktivitas sesuai dengan kebutuhan misalnya bercocok tanam didepan rumah. Penerapan vertikultur di perumahan lowokwaru, dengan desain vertikultur dinding, vertikultur gantung,vertikultur pagar, vertikultur rak, hidropinik dan aquaponik bisa mengatasi masalah pengalihan fungsinya sebuah taman.